RELIGIOUS SCHOLARS ACTIVE IN THE BOYSUN EMIRATE AND THEIR EDUCATIONAL ACTIVITIES (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the lives and scholarly-educational activities of prominent religious scholars who were active in the Boysun region of Surxondaryo province from the late 19th to the mid-20th century—Qosim Boysuniy, Azimov Ravshan Mufti, Domla Karimbek, Mulla Doʻst Nodir Boysuniy, and Norqul Shaykh Rajab ogli. The study highlights their roles in the religious education system, their academic connections with Bukhara madrasas, and the impact of Soviet-era persecution policies on religious scholars. The findings underscore Boysun’s significance as a center of religious and educational life, as well as the contributions of these scholars to the spiritual and cultural life of the local population.